Adsorption of acid fuchsin onto the chitosan–montmorillonite composite. Issue 6 (18th August 2017) - Cao, Chun-Yan; Zhang, Tian; Cong, Qiao
ABSTRACT: The chitosan–montmorillonite composites (CTS–MMT) were prepared by CTS in combination with Na-type montmorillonite (Na-MMT). The composites were characterized by X-ray diffraction and Fourier transform infrared spectroscopy. The effects of initial pH value of the solution, adsorbent dose, the mass ratio of CTS to Na-MMT, the adsorption temperature, and contact time on acid fuchsin (AF) removal efficiency were investigated. The results indicated that the CTS could be successfully intercalated into the interlayers of Na-MMT. With the increase in content of CTS, some of them may be distributed on the surfaces of the clay and the AF removal efficiency can reach 80.2% using CTS–MMT as adsorbent to treatment AF wastewater (the AF concentration 20 mg/L) under the condition of pH, 5; adsorbent dose, 5 g/L; the mass ratio of CTS to Na-MMT, 0.25:1; adsorption temperature, 40°C; and contact time, 90 min. Meanwhile, it was shown that the adsorption processes were better fitted by pseudo-second-order model and the Freundlich model.